Hakikat Makna Konsep tentang Sistem di Sekolah - Fachruddin Fachruddin; Makmur Syukri; Muammar Muammar; Salim Said; Ikhsan Hadinata; Aisyah Sitorus (Transformasi Manageria: Journal of Islamic Education Management, 2023)
The purpose of this research is to find out the principal's program in creating a school organizational system and how the principal's strategy is in forming a school organizational system. This research uses a qualitative approach with descriptive methods. The informant of this research is the school principal. Data collection techniques used are observation, interviews and documentation. Data analysis techniques using data reduction, data presentation and drawing conclusions by testing the validity of the data using credibility, transfer, dependability and suitability tests. The results of this study indicate that: the school principal is to make an organizational system and school arrangement, including making the school organizational structure contained in the Decree of the Minister of Education and Culture. Middle school, hereinafter abbreviated as SMP, is a form of formal education unit that organizes general education at the junior secondary education level. The organizational design for junior high schools has actually been regulated in Permendikbud No. 6 of 2019. Keywords: Concept Nature, the System in Schools